Soluble glucomannan isolated from Candida utilis primes blood phagocytes - Hájková, Veronika; Svobodová, Aneta; Viačková, Daniela; Číž, Milan; Velebný, Vladimír; Lojek, Antonín; El-Benna, Jamel; Kubala, Lukáš (Carbohydrate research, 2009)
It is well documented that the polysaccharide glucomannan (GM), an abundant constituent of the fungal cell wall, in the form of particulate induces strong activation of phagocytes, however, the effects of soluble GM are not known. Activation of phagocyte anti-microbial mechanisms is a crucial part of the innate host defense against invading pathogens. However, under uncontrolled inflammatory conditions they contribute to damage of surrounding tissues. Thus, to prevent these deleterious effects, the activation of phagocytes is a tightly regulated process. Therefore, in this study we analyzed the effect of soluble GM on some neutrophil functions such as reactive oxygen species production, degranulation, and receptor mobilization at the plasma membrane. Soluble GM at the tested concentrations did not stimulate oxidative burst of phagocytes directly but significantly potentiated oxidative burst in response to opsonized zymosan particles. GM induced significant phosphorylation of p47phox subunit of NADPH oxidase on Ser345. This priming effect of GM was accompanied by time and concentration dependent degranulation characterized by increased surface expression of receptors stored in neutrophil granules (CD10, CD11b, CD14, CD35, and CD66b). Degranulation was further confirmed by increase of elastase activity in media. Thus, it could be suggested that soluble GM induces priming of phagocytes connected with their degranulation, the increase of surface receptor expression, and potentiation of oxidative burst response to opsonized particles through the activation of NADPH oxidase.
Keywords: NADPH-oxidasy; rac GTP-Binding Proteins; respirační vzplanutí; Phosphorylation; Zymosan; NADPH Oxidases; Phagocytes; fagocyty; mannany; Humans; rac proteiny vázající GTP; zymosan; Mannans; Respiratory Burst; fosforylace; Candida; lidé